RANCANG BANGUN APLIKASI PENERIMAAN JASA PERBAIKAN SEPEDA MOTOR PADA BENGKEL SELARAS MOTOR BERBASIS WEBSITE - Trong, Cornelis Dehotman; Soebijono, Tony; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The workshop is one of the places where vehicles such as motor cars and placed with a variety of needs, as well as damage repair. In addition the workshop also is one of the best places to put a motor vehicle such as car and motorcycle. The service processes that occur at the workshop in synch motor still experience barriers when conducting registration service. Customers who will do the service has always been considered a new customer, the current registration process are still recorded manually.The solution to the above problem by creating an architecture application acceptance service motorcycle repair workshop on the functioning of the motor aligned to process data reception service.This application helps the process of administration of operational activities include: managing the master data includes the data, users, categories, products, services, brands, customers, motor motorcycle customers. managing transaction data covering transactions service start process, service, service, service close to the finish. Expected by the existence of this application can help management and employees in carrying out operational activities and monitoring so as to improve pelanyanan at the workshop. Keywords: Applications, Workshop, Service Improvement.